Bibliometric analysis of research output by the academics of the Faculty of Agriculture,University of Jaffna - Umashankar, L.; Ambihai, S. (National Institute of Library and Information Sciences (NILIS), University of Colombo, 2015)
This study has tried to quantify the research output of the academics of the Faculty of Agriculture, University of Jaffna during the period of 2003 to 2012. Bibliometric tools were used to analyze data. The results revealed that the total number of publications during the ten year period was 359 with the annual average of 36 publications. The highest number of papers (67 = 18%) had been published in the year 2008. Department of Agricultural chemistry top the list with 99 publications (27.6%) followed by Agricultural engineering with 81 publications (22.6%). It has been observed that the dominant format of publication is 'Abstracts' (79%). The result shows that the relative growth rate (RGR) has come down from 0.44 to 0.19 over the first five years. The mean RGR for the first five years exhibits a growth of 0.272 and similarly for the next block of five years the growth is 0.246. Doubling time increased gradually from 1.6 to 4.1 over a period of 10 years. The mean doubling time for the first five years (2003-2007) is 1.78 where as it has increased to 3.82 in the second block of five year period. Degree of collaboration during the ten years period is quite significant (0.8). Only 20% papers were single authored papers. Majority of the publications had been carried out in collaboration either by two-authors (40%) or multi authors (three to five - 33%) Only 7% had been published by more than five authors. Based on the time series trend, the expected number of publications in the year of 2015 would be 56 (18.8%). It can be suggested that the Faculty of Agriculture has to exploit more of its human potential to push their communications to get published more frequently in the journals.
Keywords: Faculty of agriculture - University of jaffna; Agriculture research; Bibliometric studies; Growth of publications